A Comparative Study of Rate of Bffithand Mortality in Lion-tailed Macaque (Macaca silenus) - Arora, B. M.; Malhotra, A. K. (Indian Forester, 1993)
Lion-tailed macaque (LTM) has been included in Sechdule-I, Part-I (Mammals) of Indian Wildlife (Protection) Act, 1972. The data on its births, deaths was collected from National Zoological Park w.e.f. January, 1962 to December, 1991 and for the year 1973 to 1990 from Zoological Park, Kanpur. The average recorded deaths and their census in these Parks during those periods have been mentioned in this study.